Species Comparison of Pre-systemic Bioactivation of Vicagrel, a New Acetate Derivative of Clopidogrel - Qiu, Zhi-xia; Gao, Wen-chao; Dai, Yu; Zhou, Su-feng; Zhao, Jie; Lu, Yang; Chen, Xi-jing; Li, Ning (Frontiers in Pharmacology, 2016)
Previously we have found vicagrel, a new acetate derivative of clopidogrel, underwent hydrolysis to 2-oxo-clopidogrel and subsequent conversions to its pharmacological active metabolite (AM) and inactive carboxylic acid metabolite (CAM). This study demonstrated the interspecies differences of the vicagrel bioactivation by comparing the critical vicagrel metabolites formation in rats, dogs and human. The pharmacokinetic studies with rats and dogs were conducted after intragastric administration of vicagrel, followed by in vitro metabolism investigation in venous system, intestinal/hepatic microsomes from rats, dogs and human. An obvious disparity was observed in system exposure to AM (99.0 v.s 635.1μg∙h/L, p<0.05) and CAM (10119 v.s 2634 μg∙h/L, p<0.05) in rats and dogs. It was shown that the cleavage of vicagrel was almost completed in intestine with great different clearance (53.28 v.s 3.643 L∙h-1∙kg-1, p<0.05) in rats and dogs. With no further hydrolysis to CAM, the greatest clearance of AM (3.26 mL∙h-1∙kg-1) was found in dog intestine. In rat plasma, 2-oxo-clopidogrel was much more extensively hydrolyzed to CAM than in dog and human. Albeit similar hydrolysis clearance and AM production was observed among hepatic microsomes of the three species, the production velocity of CAM ranked highest in dogs (7.55 pmol/min/mg protein). Therefore, the unconformity of AM and CAM exposure cross species mainly came from the metabolism of 2-oxo-clopidogrel associated largely with tissue specificity and interspecies differences of esterases. In human, the pharmacokinetics of vicagrel might be more optimistic due to less inactivation hydrolysis before reaching liver.